The Sustainable and Green Engine (SAGE) : aircraft engine of the future? - Smith, David J., active 2016, (SAGE Knowledge. Cases., 2016)
The case of the European Union's (EU) Clean Sky initiative and its sustainable and green engine programme focuses on a sector where the implications of climate change are likely to be keenly felt in the coming decades, namely air transport. It is a sector where to date there have been few green or eco innovations. The case focuses on a current EU-funded initiative designed to limit the impact of air transport on climate change. The initiative aims to foster innovation through the introduction of open rotor technology to power the next generation of short-/medium-haul airliners. This technology could potentially cut carbon dioxide emissions from commercial aircraft by 100 million tonnes per year. However, it may also prove to be a disruptive technology rendering existing aircraft and possibly some of the firms that produce them, obsolete. As well as introducing some of the features of disruptive technologies, the case highlights both the drivers for and barriers to the successful adoption of green innovations. Another important aspect of the case is that it also highlights the value of appropriate business strategies, such as the use of technology demonstrator programmes, in supporting and facilitating the adoption and diffusion of green innovations.